2022
DOI: 10.3889/oamjms.2022.9043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microscopic Decompression and Biportal Endoscopic Spinal Surgery in the Treatment of Lumbar Canal Stenosis and Herniated Disc: A One-year Follow-up

Abstract: Backgrounds. Microscopic decompression (MD) has been widely used as an alternative to open decompression. Lately, biportal endoscopic spinal surgery (BESS) - a new approach in minimal-invasive spinal surgery – has also been used with good results.  Although both groups can achieve adequate lumbar decompression, there is still a lack of evidence regarding their comparison. We aim to compare the outcomes of both techniques in a one-year follow-up. Methods. This is a retrospective study in 100 consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Following a rigorous assessment, 37 studies met the inclusion criteria and were included in this meta-analysis. 9,10,14,16,21-53 The Preferred Reporting Items for Systematic reviews and Meta-Analysis flow diagram of the literature search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Following a rigorous assessment, 37 studies met the inclusion criteria and were included in this meta-analysis. 9,10,14,16,21-53 The Preferred Reporting Items for Systematic reviews and Meta-Analysis flow diagram of the literature search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%